(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The architecture of Uzbekistan is of great importance in the formation and preservation of the rich historical fabric of this country. From its primitive roots to its modern metropolises, every building, every architectural element is an integral part of the history and culture of Uzbekistan. This abstract raises an important question about the architectural heritage of Uzbekistan and its influence on the understanding of the past. The architecture of Uzbekistan is a living testimony to the development of society, reflecting periods of prosperity and crisis, innovation and preservation of traditions, the evolution of tastes and styles. From ancient cities on the Silk Road to the modern capitals of the republic, architecture serves not only functional purposes, but also embellishes the history of Uzbekistan. This annotation helps to understand how architectural masterpieces such as the Registan in Samarkand testify to the rich heritage of this country and continue to attract the attention of both national and global researchers and travelers."